Juridical Study On The Competence of Religion Courts In Completing Syariah Banking Disputes Based On Article 55 Law Number 21 of 2008 Concerning Banking Syari'ah - M.Hidayat; Sinarianda Kurnia (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2018)
If we want to respect Law No. 3 of 2006 concerning Religious Courts, give full competence in sharia banking disputes to the Religious Courts. Including the issue of mortgages (guarantees, red) and their execution, "the trial of Article 55 paragraph (2) and (3) Law No. 21 of 2008 concerning Islamic Banking. Sharia Economics Expert Muhammad Syafii Antonio believes that the settlement of Islamic banking disputes should be the full authority of the Religious Courts. This is to ensure that the religious court's verdicts are truly in accordance with sharia law based on Law No. 3 of 2006, the Religious Courts have been given the authority to adjudicate issues of sharia economics, banking, finance and insurance based on sharia law.